2022
DOI: 10.1021/acs.jcim.1c01514
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Molecular Dynamics Simulation Studies of Realistic Eukaryotic, Prokaryotic, and Archaeal Membranes

Abstract: We present a comparative all-atom molecular dynamics simulation study of 18 biomembrane systems with lipid compositions corresponding to eukaryotic, bacterial, and archaebacterial membranes together with three single-component lipid bilayers. A total of 105 lipid types used in this study include diverse sterols and glycerol-based lipids with acyl chains of various lengths, unsaturation degrees, and branched or cyclic moieties. Our comparative analysis provides deeper insight into the influences of sterols and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 97 publications
3
41
0
Order By: Relevance
“…4 C), suggesting a more disordered membrane. Recent all-atom MD simulations of a model system of ER with a complex lipid mixture [64] reported values of APL (average 0.62 nm 2 ) and thickness (average 4.02 nm) in broad agreement with our results. Our analyses shed light on the biophysical properties of ER bilayer, showing loose packing and low ordering of lipids that may reflect membrane dynamics involved in the functions of ER.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…4 C), suggesting a more disordered membrane. Recent all-atom MD simulations of a model system of ER with a complex lipid mixture [64] reported values of APL (average 0.62 nm 2 ) and thickness (average 4.02 nm) in broad agreement with our results. Our analyses shed light on the biophysical properties of ER bilayer, showing loose packing and low ordering of lipids that may reflect membrane dynamics involved in the functions of ER.…”
Section: Resultssupporting
confidence: 91%
“…We used coarse-grained MD simulations to investigate if, with this approach, we can study the interaction of p24 with sphingomyelin, previously observed with all-atom MD simulations [63] , [64] , and observe effects associated with the presence of cholesterol ( Fig. 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recent evidence showed the RBG protein superfamily can transfer phosphatidylcholines and phosphatidylethanolamines (Neuman et al, 2022; Toulmay et al, 2022). The ER is relatively enriched in those lipid species compared to endo-lysosomes (Escribá et al, 2015; Guo et al, 2009; Horvath and Daum, 2013; Pogozheva et al, 2022; Reglinski et al, 2020; Tauchi-Sato et al, 2002; van Meer and de Kroon, 2011; van Meer et al, 2008). Despite this, the levels of phosphatidylcholine, phosphatidylserine, phosphatidylinositol, and sphingomyelin increase in the lysosome in VPS13C knockout clones (Hancock-Cerutti et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, protein-lipid membrane components were assembled through the CHARMM-GUI Replacement Method. Lipid membranes compositions were based on previous predictions and biochemistry (Escribá et al, 2015; Guo et al, 2009; Horvath and Daum, 2013; Jo et al, 2008; Pogozheva et al, 2022; Reglinski et al, 2020; Tauchi-Sato et al, 2002; van Meer and de Kroon, 2011; van Meer et al, 2008). Protein-membrane orientations were based on previous experimental approaches (Baldwin et al, 2021; Koike et al, 2019; Kumar et al, 2018; Muñoz-Braceras et al, 2019; Seifert et al, 2011; Yeshaw et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Molecular dynamics (MD) simulations have been used to study lipid organization and the formation of domains on a large scale 22 as well as comparative studies of eukaryotic, prokaryotic, and archaeal membranes 23 . Despite this, at the time of writing, there are no complete models of the Mycobacterial plasma membrane that capture the asymmetry and the range of complex lipids 24 .…”
Section: Introductionmentioning
confidence: 99%